Predicting leakage of the VERCORS mock-up and concrete containment buildings - a digital twin approach - Laurent Charpin; Jessica Haelewyn; Anass Cherki El Idrissi; Julien Niepceron; Benoît Masson; Charles Toulemonde; Guillaume Boulant; Jean-Philippe Mathieu; François Hamon; Sylvie Michel-Ponnelle; Jean-Marie Hénault; Frédéric Taillade; et al. (Acta Polytechnica CTU Proceedings)
EDF operates a nuclear power generation fleet made up of 56 reactors. This fleet contains 24 reactors designed as double-walled concrete containment building. The inner concrete containment vessel has no metallic liner and is a prestressed reinforced concrete building. The inner concrete containment vessel is designed to withstand a severe accident, in terms of mechanical and sealing behaviour. The tightness of the containment is tested every 10 years, by carrying out a pressurization test and by measuring the leak rate. The leak rate is required to be below a regulatory threshold to continue operation of the concrete containment building for the next ten years. Ageing of concrete due to drying, creep and shrinkage leads to increase prestress loss and then leak rate with time. For some containment buildings, the leak rate gets closer to the regulatory threshold with time, so important coating programs are planned to mitigate and limit the leak rate under the regulatory threshold. Therefore, it is very important for EDF to have a concrete containment building leak rate prediction tool. To address this issue, an important research program around a 1/3 scale concrete containment building mock-up called "VERCORS" have been launched at EDF. The mock-up is heavily instrumented, and its materials (concrete, prestressing cables) have been widely characterized and studied. An important numerical effort has also been made to implement structural computations of the mock-up and to capitalize these computations as well as their post-processing (so as to compare automatically with the monitoring data) in what can be called a digital twin of the mock-up. This digital twin is now used to predict the leakage of VERCORS mock-up before yearly pressure test, and also to optimize the repair programs on the real containments.